Mario Boza, Director and Founder of Costa Rica´s National Park Department (Biocenosis, 2022)
Soon after receiving his M.Sc. degree in Forestry Sciences with emphasis in Wildlands Management in IICA in 1968, Ing. Mario Boza was declared Director of the newly created Department of Costa Rican National Parks. He was immediately responsible for four national wildlands created around 1970: Volcan Poas National Park, Santa Rosa National Park, Tortuguero National Park and Cahuita National Monument. Although faced with limited financial and human resources, Mario, working with his colleague Alvaro Ugalde, proved themselves both dynamic and determined, searching for national and international donors, political allies, and volunteers. As a Peace Corps Volunteer with Mario, between 1971-1974, I was assigned to work with Mario and Tropical Science Center scientists (Drs. Holdridge, Tosi and Skutch), in an inventory to locate future national parks and biological reserves. For most potential areas, I travelled alone or accompanied by biologists or guides, but Mario accompanied me on two trips. The second trip was in 1975 to the future Corcovado National Park and occurred after Mario was director and I professor at the Environmental Sciences School. I had visited Corcovado several times during the inventory, and I wanted Mario to visit Corcovado for several reasons; one of the majors because it still hadn’t been declared a national park and was under great pressure to be destroyed for agriculture, goldmining, and a transnational forestry/development company. We went, Mario was convinced and using our past reports and their political contacts, Mario and his colleague, Alvaro Ugalde, then director of the Costa Rican National Parks Department, persuaded Costa Rican President Daniel Oduber to decree Corcovado National Park in August of 1975.
Keywords: Department of Costa Rican National Parks; Peace Corps; Tropical Science Center; inventory of potential national parks and biological reserves; Corcovado National Park